Panorama of étiologies of headaches seen on the scanner at the CNHU-HKM of Cotonou from 2016 to 2019 - ADJADOHOUN, SONIA B M G; VIDEGLA, Boris; AKANNI, DWMM; YEKPE AHOUANSOU, patricia; SAVI DE TOVE, KM; BIAOU, OLIVIER; ADJIBABI, WASSI (My University, 2022)
Abstract Introduction: Headaches are one of the main indications for CT in our daily practice. The purpose of this study is to assess the contribution of CT scans in the etiological research of headaches. Materials and Methods: This was a cross-sectional, descriptive study with retrospective collection carried out over a period of 46 months, in the University Clinic of Medical Imaging of CNHU-HKM in Cotonou (BENIN). We collected all CT scan reports for headaches during the study period. The variables studied were the socio-demographic data, the type of headaches, the computed tomography data. Results: 5678 cranio-encephalic and sinus scans were recorded, including 353 (6,2%) for an indication of headache. The average age is 43 years with a standard deviation of 4 years at 91 years. A female predominance was noted with a sex ratio (M/F) of 0.72. Chronic headaches were predominant (87% of cases). The CT scan was normal in 38.5% of cases, and objectified lesions consisting mostly of sinus abnormalities (47.6%) followed by intracranial hemorrhages (3.7%), brain tumors (2.3%) and subarachnoid hemorrhages (1.1%). Conclusion: The cerebral scanner is essential for the etiological assessment of headaches in the absence of MRI.
Keywords: Headaches; scanner; etiology; Benin